COOPERATION AMONG COOPERATIVES: IS GOVERNMENT INTERVENTION AN OBSTACLE OR A FACILITATOR? - Félix, Juan Enrique Santana (International Journal of Cooperative Law, 2024)
This article examines the cooperation among credit unions in Puerto Rico, focusing on the development of these entities, the legislation that governs them, and the challenges that arise when requesting the creation of branches. It explores cooperative principles, the doctrine supporting them, and the role of government intervention in this context. The importance of maintaining solidarity among cooperatives to meet common needs and avoid harmful competition between cooperatives is discussed. Specific cases that have generated controversies between cooperatives and the state regulation governing the opening of new branches are analyzed, highlighting the need for transparency and fairness in this process.